2020
DOI: 10.1080/09669760.2020.1796416
|View full text |Cite
|
Sign up to set email alerts
|

A growing interest in early childhood’s contribution to school readiness

Abstract: 's report on equality and education published in the mid-1960s (Coleman 1966) made a blunt statement that children, especially the 'non-white children' in the USA were not enjoying equal opportunities in education, as they were not coming to school 'ready'. Reading the report now, the race and class bias in system is very apparent; it sought to compensate for the perceived social-cultural-economic characteristics of the home and family environment that was emphasised as playing a decisive role in children's sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The teachers felt more pressure to teach early literacy skills seen as a prerequisite for primary school readiness than the pre-service teachers (Whitebread & Coltman, 2015). This pressure on pre-school teachers rapidly advances pre-school education institutions towards becoming mini-primary schools (Needham & Ülküer, 2020;). Some studies have shown that giving structured examples -such as worksheets -to pre-school children as part of their preparation for primary school helps them to be more successful when they start primary school and can increase their school readiness (Anning, 2010).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The teachers felt more pressure to teach early literacy skills seen as a prerequisite for primary school readiness than the pre-service teachers (Whitebread & Coltman, 2015). This pressure on pre-school teachers rapidly advances pre-school education institutions towards becoming mini-primary schools (Needham & Ülküer, 2020;). Some studies have shown that giving structured examples -such as worksheets -to pre-school children as part of their preparation for primary school helps them to be more successful when they start primary school and can increase their school readiness (Anning, 2010).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A child who starts their school session needs to be well prepared to accept a new atmosphere when they step into the classroom. School readiness can be used to highlight support for children's social, emotional, linguistic, and a wide range of communication abilities, especially to promote equity for children from "disadvantaged" backgrounds (Needam & Ülküer, 2020). Having school readiness skills by the age of 4 affects academic achievement in primary school long-term, and social and emotional competence is a crucial factor of school readiness (Ricciardi et al, 2021).…”
Section: The Readiness Skills Of Childrenmentioning
confidence: 99%
“…), and provides an "ideal" universal image of the child that benefits political ECEC outcomes. All of these fail to account for new and alternative perspectives of school readiness, reflected in Needham and Ülküer (2020) who call for a recentring of education as a site for social justice. Spyrou (2018) argues much of the current approach to ECEC curriculum delivery and assessment is not congruent with the image of the child as active, autonomous, powerful, and capable of having a voice in matters that involve them.…”
Section: Reclaiming Research and Curriculum Practicesmentioning
confidence: 99%